Kosentrasi COD dan Nitrit di Permukiman Desa Bakau Besar Laut kecamatan Sungai Pinyuh Kabupaten Mempawah - Ria Risti Astanti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The settlements in RW 3 and RW 4 of Bakau Besar Laut village, Sungai Pinyuh district, covers an area adjacent to two small industries, namely a shrimp farm and copra processing with no WWTP facility, generating domestic wastes that potentially pollute local settlements and farms. This research has the purpose of identifying the COD and Nitrit contents in the settlement by testing the drainage water quality in the local settlements and farms. Grab Sampling method was used to sample the water, whereas Mann Whitney method served in statistical test. Result of analysis shows that COD and Nitrit concentration in each drainage has surpassed the quality standard specified in Government Regulation (PP) no. 82 of 2001. Based on the results of Mann whitney statistica test, it was found that the BOD, Grease and Fat content has a radius of 700 m > 1700 m (agricultural drainage) with sig value of 0.677 > 0.05; 500 m > 1500 m (inhabitants’ drainage) with sig value of 0.936 > 0.05. Recommendations include clean water treatment (PAM/drinking water company) with intake from Bakau Besar Laut river and garbage sorting based on their characteristics (e.g. organic, anorganic and toxic and hazardous), establishing WWTP (Waste Water Treatment Plant) for shrimp farms and copra processing industries as well as establishing animal waste-based Biogas processing plants as sources for fuel and compost fertilizers that can be reutilized by the people.